Accelerator for agglomeration in sequencing economics: 'leased' industrial zones - Akifumi Kuchiki (Economies, 2023)
This paper identifies the importance of reducing fixed costs for establishing industrial zones as part of an agglomeration policy. China's economic growth has been driven by the agglomeration of manufacturing firms via industrial zones that attract foreign direct investment. This investment enables the export of products by importing intermediate capital goods. According to the new trade theory of spatial economics, the number of firms in an agglomeration is inversely proportional to the fixed costs. The main accelerator of agglomeration after the master switch is the formation of segments that reduce firms' fixed costs. Via a factor analysis of manufacturing agglomeration segments in sequencing economics, this paper finds that 'leased' industrial zones are accelerator segments in the formation process of manufacturing agglomerations.
Keywords: 330; accelerator segment; leased industrial zones; sequencing economics; manufacturingagglomeration; fixed costs; spatial economics